Legitimacy Building in the Evolution of Small-Firm Multilateral Networks: A Comparative Study of Success and Demise - Human, Sherrie E.; Provan, Keith G. (Administrative Science Quarterly, 2000)
This article reports a longitudinal examination and comparison of two multilateral networks of small and medium-sized firms in the U.S. wood-products manufacturing industry. The research focused on how each of these networks built legitimacy over the course of their early evolution, from the pre-network field, to initial formation and growth, and toward sustainment, culminating in the success of one and the demise of the other. Our findings demonstrate that despite differences in their early bases of support, which resulted in very different strategic emphases, the two networks ultimately had to address three conceptually distinct dimensions of legitimacy—the network as form, the network as entity, and the network as interaction. Based on the findings, we develop specific propositions and draw some tentative conclusions about how legitimacy is established in multilateral networks and how the failure to build legitimacy across the three dimensions may lead to network collapse.